Verbal and Nonverbal Mismatch Negativity in Children with Typical Development: Variables Analysis - de Souza,Amália El Hatal (2021)
Abstract Introduction Mismatch negativity (MMN) is a promising instrument for the investigation of different auditory disorders, as it does not need behavioral responses. Objective To analyze the influence of the ear, gender and age variables in the MMN in children with typical development; and to compare the different measures of this potential, using verbal and nonverbal stimuli in the sample studied, providing reference values. Methods Observational, descriptive, cross-sectional, quantitative study, with 23 children, aged from 5 to 11 years and 11 months old, divided by age group. Mismatch negativity was performed using verbal and nonverbal stimuli, and the data was analyzed by means of the statistical Student t-test. Results No significant differences were noted for the ear, gender and age variables in the MMN with both stimuli. There were significant differences for the latency, duration and area variables when the stimuli were compared. The reference values established for nonverbal stimuli were: latency 249.8 milliseconds, amplitude 2.28 µv, duration 82.97 milliseconds, and area 137.3 microvolt x microseconds (μVx μs); as for the verbal stimuli, they were: latency 265.3 milliseconds, amplitude - 2.82 µv, duration 110.5 milliseconds, and area 225.5 microvolt x microseconds (μVx μs). Conclusion The variables studied did not influence the recordings of the MMN. Latency, duration and area of the MMN with verbal stimuli were higher. It was possible to furnish reference values for children with typical development in the age group studied.